Ethical considerations in designing and testing robots for children in educational settings - Arriaga, P.; Neto, I.; Correia, F.; Soares, A. (Social Robots in Education: How to effectively introduce social robots into classrooms, 2025)
The integration of social robots into children’s lives, whether for educational, rehabilitation, therapeutic, or entertainment purposes, has progressed in recent years, requiring addressing ethical concerns that extend beyond the standard ethical requirements applied to human research. This chapter discussed ethical issues surrounding developing and investigating social robots intended for children in educational settings to ensure their safety, positive development, and well-being. First, we reviewed current approaches to using social robots in educational settings. We discussed the benefits and potential concerns in child-robot interaction (CRI), including issues of attachment and dependency, obedience, reduction of human interaction, and accountability. Secondly, we reviewed the main ethical principles and guidelines, professional codes of conduct, and regulations relevant to CRI. Third, we review and discuss the methodological research aspects implemented for the design of robots and assessing their impact on children by outlining some ethical practices for conducting research. Finally, we explored the implications of integrating social robots into educational settings, focusing on their deployment and long-term use in classrooms, along with crucial aspects of sustainable research practices aiming to help shape future directions in this field.